Arte/Cidade. : A Cidade e suas Histórias -. - Coelho, Teixeira; Farias, Agnaldo; Katz, Helena; Labaki, Amir; Machado, Arlindo; Mammi, Lorenzo; Matos, Olgária Chain Féis; Ohtake, Ricardo; Peixoto, Nelson Brissac; Garcias dos Santos, Laymert; Subirats, Eduardo; Tassinari, Alberto; et al. (São Paulo : Arte/Cidade - Grupo de intervenção Urbana - SESC - Secretaria de Estado da Cultura de São Paulo, 1994)
Arte/Cidade is a project of urban interventions realized in São Paulo, Brazil, since 1994
Sumner, Anne Marie ; Antunes, Arnaldo ; Yamauchi, Susana ; Giannotti, Marco ; Saggese, Antonio ; Gross, Carmela ; Tragtenberg, Livio ; Diaz, Enrique ; Vasconcellos, Cássio ; Santos, Eder ; Fajardo, Carlos ; Furtado, Jorge ; Omar, Arthur ; Resende, José ; Klotzel, André ; Omar, Arthur ; Guerra, Abilio ; Valle, Marco do ; Tonacci, Andrea ; Muylaert, Anna ; Lescher, Artur ; Matuck, Artur ; Vicente, Carlos Fadon ; Reichenbach, Carlos ; Neto, Cecilio ; Fujocka ; Lacaz, Guto ; de Freitas, Iole ; Garcia, José Wagner ; de Barros, Lenora ; Donasci, Otavio ; Silveira, Regina ; Mano, Rubens ; Jungle, Taden ; Knudsen, Taden ; Silveira, Walter ; Caldas, Waltercio ; Sukorski, Wilson
Catalogus 3: Arte/Cidade : Cidade sem janelas (Portugees), ongepag. : ill.
biografie
Portugees & Engels
boek
Keywords: Sao Paulo